Erasmus+ and Educational Inspectorate - Alonso de Castro, María Goretti; Dupraz, Florence (Avances en Supervisión Educativa, 2026)
This article examines the role of the Educational Inspectorate within the Erasmus+ programme, drawing on the presentation delivered by Florence Dupraz at the ADIDE Madrid 2025 Conference. It explores the programme’s main components — educational mobility, international cooperation and Jean Monnet activities — and analyses their contribution to school improvement and institutional development. The article also highlights the growing involvement of inspectorate staff in advising, supporting and evaluating European projects, as well as their participation in professional development mobilities that foster comparative perspectives on educational systems. Particular attention is given to the new School Development Partnerships action, which encourages structured collaboration between local educational authorities and schools from different countries, offering opportunities for multi‑level innovation and system-wide development. The analysis concludes that Erasmus+ functions as a catalyst for educational transformation and as a meaningful pathway for the professionalisation and strategic strengthening of the Educational Inspectorate.